2020
DOI: 10.1002/app.49335
|View full text |Cite
|
Sign up to set email alerts
|

The influence of several silicates on the fretting behavior of UHMWPE composites

Abstract: Five kinds of silicates (attapulgite, kaolin, montnorillonite, synthetic mica, and talc) reinforced ultra‐high molecular weight polyethylene (UHMWPE) composites were prepared. The fretting performance of the composites was investigated using an oscillating reciprocating friction and wear tester in a ball‐on‐plate mode. The thermodynamic property and crystallinity of the composites were evaluated, and the worn morphology was also observed. Result shows that the heat‐resistance and the crystallinity of the compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Water was a kind of poor lubricant, because of its low viscosity and small load‐bearing capacity. [ 14 ] The lubrication effect of water was not ideal, but by adding some additives, the tribological performance of water can be significantly improved. [ 15 ] Some studies revealed that polyethylene glycol (PEG) can effectively improve the lubrication performance.…”
Section: Introductionmentioning
confidence: 99%
“…Water was a kind of poor lubricant, because of its low viscosity and small load‐bearing capacity. [ 14 ] The lubrication effect of water was not ideal, but by adding some additives, the tribological performance of water can be significantly improved. [ 15 ] Some studies revealed that polyethylene glycol (PEG) can effectively improve the lubrication performance.…”
Section: Introductionmentioning
confidence: 99%
“…Adding fillers such as inorganic particles, [ 20 ] carbon additives, [ 21 ] and graphene [ 22 ] to reinforce them is the most straightforward and most efficient modification method. Wang et al [ 23 ] used five different silicates to enhance UHMWPE and compared the effects of different fillers on the fretting properties, thermodynamic properties, and crystallinity of composite materials. However, these studies usually use non‐renewable resources as fillers.…”
Section: Introductionmentioning
confidence: 99%